Evaluation of sexuality of obese patients before and after bariatric surgery: an integrative review (Research, Society and Development, 2023)
Introduction: Obesity is considered a global epidemic, due to its rapid growth, being a public health problem that affects the physical and psychological health of the individual. In this context, changes in sexual and reproductive function are inserted, since obesity becomes a difficulty for the individual to recognize his social role as a subject, especially in the experience of sexuality. Objectives: To evaluate the sexuality of obese people before and after bariatric surgery. Methods: This is an integrative literature review, descriptive and analytical, carried out between April and May 2022. Results: Of the 17 selected articles, it was observed that most patients reported improvement in sexual performance after bariatric surgery, identified by increased energy/spirit/less tiredness, increased sexual performance and libido, interference from weight loss and increased duration of the sexual act, as well as improvement in psychosocial factors, such as more self-esteem, desire/ interest and less shame. It was observed that more studies were carried out in women than in men, and that the expression of sexual behavior and function between genders differs, both from a biological and psycho-relational point of view. Conclusion: Considering that sexuality is an important factor that influences the individual's quality of life, its improvement after BS generates positive physical and emotional repercussions, which cannot be underestimated in clinical practice.